Chusquea calderoniae (Poaceae: Bambusoideae), a new species of C. subg. Chusquea endemic to the Espinhaço Range, Brazil - de A. Vidal, Kaio Vinicius; Souza, Murilo José O.; Welker, Cassiano A. Dorneles; Oliveira, Iasmin Laiane C.; Clark, Lynn G.; Oliveira, Reyjane P. (Phytotaxa, 2023)
Chusquea is the richest genus of Neotropical bamboos, occurring from Mexico to Argentina and Brazil, with 198 accepted species. In Brazil, 49 members of this genus have been recorded, with the Eastern region being its main center of diversity, especially in the states of Bahia, Minas Gerais, and Rio de Janeiro. The Espinhaço Range, found within this region, is considered the largest mountain complex in Brazil, including campo rupestre, caatinga, and cerrado vegetation types and transitional types among these, which explains the particular plant diversity of this region. Our recent taxonomic studies on Brazilian Chusquea subg. Chusquea indicated the presence of a new species herein described and illustrated, named C. calderoniae. It is morphologically related to the C. meyeriana informal group, being most similar to C. attenuata, but differing by the shape of the central bud and the length of the spikelet structures. The new species is endemic to the Espinhaço Range, occurring in riparian forest on the flanks of Pico das Almas, Chapada Diamantina, Bahia, and the Diamantina Plateau in Minas Gerais state, associated to campo rupestre vegetation, in contrast to C. attenuata, which occurs in the Atlantic rainforest in the states of Minas Gerais and Rio de Janeiro.